Դարձվածքներն արդի մամուլում - Անուշ Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
Mass media concept in relatively new accepted term. It includes three powerful means of information, press, radio, and television. Being one of the means of mass information and propaganda, press is also a very powerful weapon of political struggle.
Keywords: Journalism; The periodical Press, etc.; Language and Literature